Rational Choice Theory and Interest in the "Fortune of Others". (November 2017) - Paternoster, Ray; Jaynes, Chae Mamayek; Wilson, Theodore
Objectives: We test the relationship between other-regarding preferences (concerns for other people) and intentions to drink and drive and whether these preferences condition the effect of sanction threats on willingness to drink and drive. Methods: A sample of university undergraduates played common economic games (dictator and ultimatum games) and responded to a hypothetical scenario about drinking and driving. Ordinary least squares regression models were used with the full sample and then separate samples for those with differing levels of other-regarding preferences (social preferences). Results: Net of other factors including sanction threats, demographics, measures of individual propensity, and previous experience with drinking and driving, those with strong other-regarding preferences (as indicated by responses to dictator and ultimatum games) were less likely to state that they would drive while drunk under the conditions described by the scenario. In support of differential deterrence, the self-interested were deterred by sanction threats, but those with stronger other-regarding preferences were not deterred by the perceived certainty of sanctions. Conclusions: Our findings speak to the importance of more than self-interest in explaining antisocial behavior and thereby expanding the conceptual boundaries of rational choice theory to include more than self-interest.